Feasibility of accelerated partial breast irradiation with volumetric-modulated arc therapy in elderly and frail patients. Issue 1 (December 2015) - Riou, Olivier; Fenoglietto, Pascal; Bourgier, Céline; Lauche, Olivier; Boulbair, Fatiha; Charissoux, Marie; Ducteil, Angélique; Aillères, Norbert; Lemanski, Claire; Azria, David
Abstract Background Accelerated partial breast irradiation (APBI) is an option for adjuvant radiotherapy according to ASTRO and ESTRO recommendations. Among the available techniques, volumetric-modulated arc therapy (VMAT) is attractive but has not been extensively studied for APBI. This study assessed its feasibility, tolerance and early oncological outcomes. Methods We analysed the data of nine patients (median age 74 years) with ten lesions (one bilateral cancer) treated from May 2011 to July 2012 with APBI using VMAT. The radiation oncologist delineated the surgical tumour bed, and added an 18 mm isotropic margin to obtain the planning target volume (PTV). The dose was 40 Gy prescribed in 4 Gy fractions given twice a day over five days. Patients were regularly followed for toxicities and oncological outcomes. Results Mean PTV was 100.0 cm3 and 95 % of the PTV received a mean dose of 99.7 % of the prescribed dose. Hot spots represented 0.3 % of the PTV. 6.2 %, 1.6 % and 0.3 % of the ipsilateral lung volume received 5 Gy (V5Gy ), 10 Gy (V10Gy ) and 20 Gy (V20Gy ), respectively. Regarding the contralateral lung, V5Gy was 0.3 %, and V10Gy and V20Gy were nil. V5Gy accounted for 3.1 % of the heart. An average 580 monitor units were delivered. No acute or late grade ≥ 2 toxicities were observed. With a median follow-up of 26 months, no relapses occurred. Conclusion In our study, VMAT allowed optimal dosimetry with consequential high therapeutic ratio in elderly and frail patients.